The prevalence and risk factors of kidney disease in first degree relatives of patients with ESRD treatment – single center study - Abbas, Rabeea; Elahi, Tabassum; Manan, Shumaila; Suraj (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the prevalence and risk factors of kidney disease in first degree relatives of patients undergoing treatment for end-stage renal disease. Method: The prospective, cross-sectional study was conducted at the Sindh Institute of Urology and Transplantation, Karachi, from May 1 to July 31, 2021, and comprised patients undergoing treatment for end-stage renal disease at the pre-transplant out-patients clinic, and their first degree relatives. Risk factors of chronic kidney disease, including age, gender, body mass index, hypertension, diabetes mellitus, and the causes of index cases were investigated alongside proteinuria, haematuria and estimated glomerular filtration rate. Diagnosis was made according to the criteria of the National Kidney Foundation-Kidney Disease Outcomes Quality Initiative. The participants were divided chronic kidney disease group 1, and healthy group 2. The risk factors were compared between the groups. Data was analysed using SPSS 22. Results: Of the 1,406 subjects assessed, 266(19%) were ESRD patients; 175(65.8%) males and 91(34.2%) females with mean age 34.04±11.19 years. 1,140(81%) first degree relatives of these 266 ESRD patient were assessed; 595(52.2%) males and 545(47.8%) females with mean age 36.78±13.76 years. Among the relatives, 146(12.8%) had chronic kidney disease out of which 54 (4.7%) were already aware of their underlying disease. Older age, hypertension and diabetes mellitus were among the risk factors for chronic kidney disease (p<0.05), while gender was not significantly different between groups 1 and 2 (p>0.05). The relatives of index cases with underlying stone disease were at higher risk of haematuria 39(22.4%), whereas the relatives of index cases with chronic glomerulonephritis were at higher risk of proteinuria 67(28.03%) compared to index cases of other kinds (p<0.05). Conclusion: Screening in the high-risk population might help to identify early chronic kidney disease patients for making suitable interventions to prevent disease progression. Key Words: ESRD, First degree relatives, CKD.